Respiratory system as the main determinant of dyspnea in patients with pulmonary hypertension. (23rd March 2022) - Mitrouska, Ioanna; Bolaki, Maria; Vaporidi, Katerina; Georgopoulos, Dimitris
Abstract: Dyspnea on exertion is a devastating symptom, commonly observed in patients with pulmonary hypertension (PH). The pathophysiology of dyspnea in these patients has been mainly attributed to cardiovascular determinants and isolated abnormalities of the respiratory system during exercise, neglecting the contribution of the control of the breathing system. The aim of this review is to provide a novel approach to the interpretation of dyspnea in patients with PH, focused on the impact of the control of the breathing system during exercise. Exercise through multiple mechanisms affects the (1) ventilatory demands, as dictated by respiratory center activity, (2) actual ventilation, and (3) metabolic hyperbola. In patients with PH, exertional dyspnea can be explained by exercise‐induced alterations in these variables. Compared to healthy subjects, at a given CO2 production during exercise, ventilatory demands in patients with PH are higher due to metabolic acidosis (early reaching the anaerobic threshold), hypoxemia, and excessive upward movement of metabolic hyperbola owing to abnormal exercise response of dead space to tidal volume ratio. Simultaneously, dynamic hyperinflation and respiratory muscles weakness decreases the actual ventilation for a given respiratory center activity, creating a dissociation between demands and ventilation. Consequently, a progressive increase in ventilatory demands and respiratory center activity occurs during exercise. The forebrain projection of high respiratory center activity causes exertional dyspnea despite the relatively low ventilation and significant ventilatory reserve. This type of analysis suggests that the respiratory system is the main determinant of exertional dyspnea in patients with PH, with the cardiovascular system being an indirect contributor.